Akibat Pembatalan Wasiat terhadap Harta Waris yang Telah Dialihkan Kepada Pihak Ketiga: Studi Kasus Putusan Pengadilan Negeri Nomor 656/Pdt.G/2022/PN Jkt.Sel (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Inheritance law is part of family law that is closely related to human life.  This is because all living humans will definitely experience death.  Inheritance can occur if it meets the following three conditions, namely there are people who die (heirs), there are people who are still alive who are entitled to the heir to the heir (heirs), and there is a relics of heirs (inheritance).  Inheriting is to replace the rights and obligations of someone who has died.  In the Civil Code, there are two ways that underlie a person can inherit the inheritance of the heir, namely inheriting according to the provisions of the Law (AB Intestato) and inheriting based on a will (testamentair).  Inheriting based on the law, namely if the heirs are entitled to inheritance due to blood relations or family relations with heirs.  While inheriting with a will because during his lifetime the heir made a will that wrote his final desire for the property he left behind.  This will is permitted with the provisions stipulated in the Civil Code.  This study discusses the consequences of canceling a will to inheritance that has been transferred to third parties based on the decision of the South Jakarta District Court Number 656/Pdt.G/2022/PN JKT.Sel.  With a normative juridical research method and reviewing more in various theories, concepts, and legislation concerned with the discussion in the study using the norm system as the main reference, it can be concluded that for dispute objects that have been sold or transferred can not be withdrawn, but the sale of the object must be divided to the heirs who are entitled to the law.